Universal Stress Protein Exhibits a Redox-Dependent Chaperone Function in Arabidopsis and Enhances Plant Tolerance to Heat Shock and Oxidative Stress - Jung, Young Jun; Melencion, Sarah Mae Boyles; Lee, Eun Seon; Park, Joung Hun; Alinapon, Cresilda Vergara; Oh, Hun Taek; Yun, Dae-Jin; Chi, Yong Hun; Lee, Sang Yeol (Frontiers in Plant Science, 2015)
Although a wide range of physiological information on Universal Stress Proteins (USPs) is available from many organisms, their biochemical and molecular functions remain unidentified. The biochemical function of AtUSP (At3g53990) from Arabidopsis thaliana was therefore investigated. Plants over-expressing AtUSP showed a strong resistance to heat shock and oxidative stress, compared with wild-type and Atusp knock-out plants, confirming the crucial role of AtUSP in stress tolerance. AtUSP was present in a variety of structures including monomers, dimers, trimers, and oligomeric complexes, and switched in response to external stresses from low molecular weight (LMW) species to high molecular weight (HMW) complexes. AtUSP exhibited a strong chaperone function under stress conditions in particular, and this activity was significantly increased by heat treatment. Chaperone activity of AtUSP was critically regulated by the redox status of cells and accompanied by structural changes to the protein. Over-expression of AtUSP conferred a strong tolerance to heat shock and oxidative stress upon Arabidopsis, primarily via its chaperone function.